Introducing Jakarta EE CDI : contexts and dependency injection for Enterprise Java Development - Saeed, Luqman (APress, 2020)
Discover the Jakarta EE Contexts and Dependency Injection (CDI 2.0) framework which helps you write better code through the use of well-defined enterprise Java-based components and beans (EJBs). If you have ever wanted to write clean Java EE code, this short book is your best guide for doing so: you will pick up valuable tips along the way from your author's years of experience teaching and coding. Introducing Jakarta EE CDI covers CDI 2.0 in detail and equips you with the theoretical underpinnings of Java EE, now Jakarta EE. This book is packed with so much that by the end of it, you will feel confident to use your new-found knowledge to help you write better, readable, maintainable, and long-lived mission-critical software. You will: Write better code with the Jakarta EE Contexts and Dependency Injection (CDI) framework Work with the powerful, extensible, and well-defined contextual life cycle for components Use CDIs mechanism for decoupling application components through a typesafe event API Build typesafe interceptors for altering the behaviour of components at runtime Harness the well-defined qualifier system for easy isolation of beans Convert almost any valid Java type to a CDI managed bean with CDIs producer mechanism.